The Influence of Social Media in Brand Awareness, Word of Mouth, Intention and Donation Decisionat Rumah Zakat - Mulyono, Dedi; Syamsun, Muhammad; Najib, Mukhamad (Jurnal Aplikasi Manajemen, 2016)
This study was conducted for examining the influence of social media in brand awareness, word of mouth, and intention to donate and decision making to give donation at Rumah Zakat, Indonesia. Social media as an exogenous variable. Endogenous variables consist of brand awareness, word of mouth (WOM), willingness to donate, and decision to give donation. This study uses primary data that was collected from 156 respondents which active on social media. The analysis method applies the estimation model of Structural Equation Modeling (SEM) that operated by SmartPLS program version 2.0. The result revealed that social media has significant influence to the word of mouth and brand awareness of Rumah Zakat. Brand awareness of Rumah Zakat significantly gives effect in marketing of word of mouth and willingness to donate. The establishment of word of mouth's marketing significantly effect to willingness to donate. Willingness to donate significantly influences the decision of giving donation. Meanwhile, social media indirectly influence in willingness to donate to Rumah Zakat.